Pengaruh pemberian yogurt sinbiotik tepung pisang tanduk terhadap profil lipid tikus sindrom metabolik - Zana Fitriana Octavia; Kis Djamiatun; Nyoman Suci (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2017)
Background: The metabolic syndrome, which is characterized by hyperglycemia, obesity, dyslipidemia, hypertension, prothrombic and proinflamatory state, is a risk factor for cardiovascular disease and diabetes mellitus. The synbiotic yogurt of tanduk banana (Musa paradisiaca fa. corniculata) flour contains lactic acid bacteria, fructooligosaccarides, flavonoids, and vitamin C which all of them play role in improving the lipid profile.Objective: The aim of this study was to prove the effect of synbiotic yogurt of tanduk banana flour on lipid profile of metabolic syndrome rats.Method: This study was an true experimental with pre-post test control group design. The subject of this study were 18 metabolic syndrome male Wistar rats divided into 3 groups,i.e control group (standart diet), intervention group I (standart diet and synbiotic yogurt of banana flour 0,009 ml/g weight/day), and intervention group II (standart diet and synbiotic yogurt of banana flour 0,018 ml/g weight/day). The intervention period was 2 weeks. Different test before and after intervention used paired t-test. The difference test between groups used One-Way ANOVA and Kruskal wallis.Results: The result showed that both of intervention group improved lipid profile significantly (p<0,05). The intervention group II showed more effective improvement of lipid profile significantly (p<0,05) than intervention group I. The intervention group II decreased triglycerides level 41,56%; total cholesterol level 41,39%; LDL-cholesterol level 57,5%; and increased HDL-cholesterol level 139,62%.Conclucion: The intervention of synbiotic yogurt of tanduk banana flour can decrease triglyceride level, total cholesterol level, LDL-cholesterol level, and increase HDL-cholesterol level.